ответ:здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте
Объяснение:здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте здравствуйте
б) - а - (m - a + p) = - a - m + a - p = (a - a) - m - p = - m - p
в) m - (a + m) - (-a - m) = m - a - m + a + m = (a - a) + (m - m) + m = m